Development of environmental friendly coagulant for the innovative purification of urban and agricultural runoff - Tajudin, Nor Syuhada (Universiti Sains Malaysia, 2015)
Presently, natural coagulant is an organic creation founded from polysaccharides or natural polymers has emerged to be a global interest due to the simplicity of operation, wide availability, biodegradable, and relatively low cost. This study aims to develop an environmental friendly coagulant from rice husk for the purification of urban and agricultural runoff by examined the effectiveness for turbidity, Total Suspended Solid (TSS) and Chemical Oxygen Demand (COD). The operating parameters including the coagulant dosage, pH, temperature, slow mixing intensity and contact time were evaluated. Result showed that the optimum dosage for urban and agricultural runoff was 75 mg/L and 175 mg/L, respectively. Urban runoff recorded 90% turbidity reduction, 73% of COD and TSS removal of up to 89% and the highest of turbidity, COD and TSS reduction for agricultural runoff of 95%, 74% and 88%, respectively. The newly developed coagulant was pH independent to maintain at relatively high performance at a wide pH range with the requirement of less than 50 minutes for the settlement of flocs. Morphological study showed that the derived rice husk coagulant contains high silicon element. The findings illustrated the potential of rice husk derived coagulant for the purification of contaminated wastewater.